MAMPU MENJELASKAN PENGERTIAN SUPERVISI PENDIDIKAN, TUJUAN UMUM, DAN KHUSUS SUPERVISI PENDIDIKAN - Takdirmin; Nurul Safitri; Nur Azizah; Wahyuni; Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Educational administration and educational supervision are two essential aspects of educational management that play a significant role in improving the effectiveness and efficiency of achieving educational goals. Educational administration encompasses various management functions, including planning, organizing, directing, coordinating, supervising, and financing, which are carried out systematically to optimize the utilization of educational resources. Meanwhile, educational supervision functions as a form of professional development aimed at improving the performance quality of teachers and educational personnel in the learning process. This study aims to examine the concepts of educational administration and educational supervision as well as their roles in enhancing the quality of school management and teaching–learning processes. The method employed is a descriptive qualitative approach through a literature review by analyzing relevant books and scholarly journals. The findings indicate that effective educational administration and collaborative, continuous educational supervision can enhance teacher professionalism, learning effectiveness, and the creation of a conducive school environment. Therefore, the integration of educational administration and supervision is an important factor in supporting students’ academic and non-academic success